Evaluasi Pelaksanaan Proses Pembelajaran Kelas IX SMP Negeri 4 Lubuklinggau - Oshea Miranda; Dyah Ayu Agustin; Tarisa Juwa Mey Pranata; R.A Ramadona; Sulistiyono Sulistiyono (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Teachers, students, and learning materials interact during the learning process in a classroom setting. The study's goal was to ascertain how the scientific learning process was implemented at SMP Negeri 4 Lubuklinggau. Descriptive qualitative research is what this study is. Two pupils from class IX and the science instructor for the ninth grade are the sources of the research data. Interviews, observations, and documentation were employed as data gathering methods. Source triangulation is employed in the data validity assurance technique, the Miles and Huberman method is utilized for data analysis, and the CIPP (context, input, process, product) approach model is employed. The evaluation of the learning implementation process, specifically the learning process of science teachers at SMP Negeri 4 Lubuklinggau, is described as follows: (1) pre-instructional stage (2) instructional stage (3) evaluation stage and no further. This is evident from the analysis of findings and discussion. Even if the learning process is limited by a number of issues, including the issue of infrastructure and facilities, teachers are still able to carry it out effectively.